THE EFFICIENCY OF TOLERANT (PASSIVE) ADAPTATION UNDER THE CONDITIONS OF EXPERIMENTAL POLYTRAUMA - M. L. Lebed (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The model of multiple skeletal injuries was reproduced in two groups. 22 animals of the 1st group had stabilization of the right forearm bones and left shin with spoke external fixation device of 2 subsystems with followed osteotomy of the bones of respective segment in the middle third under general anesthesia. During the experiment the injection of dexamethasone and adrenaline during the first twenty-four hours after multiple skeletal injuries prevented the reduce the intensity of the metabolic processes, that was proved by close to initial values of oxygen consumption and carbon dioxide emissions. But to the third day there was no any difference in the metabolic activity in rabbits having and not having adrenaline and dexamethasone. The animals had adrenaline and dexamethasone turned to be in more severe clinical situation. As a result of «normal» intensity of metabolic processes in rabbits during the near time period after trauma there was decrease of survival from 45,5 % to 7,7 %.